AESTHETIC MANIFESTATIONS OF CIVILITY –MYTH, IMAGE, SYMBOL, ART - Markova, Ilinida (E-Journal VFU, 2024)
To search for the ground of the creative genius, for its "communication" through the work, refracted through the prism of subjectivity, is the most difficult goal for the aesthete - the one who is both creator and audience. Understanding the essence of art as sublimity in the worldof eidetic nature must distance the "ignorant" from its artefacts. Art should not educate - that would make it accessible; it should hinder, precisely to preserve its perfection, it should preserve itself through itself.
Keywords: idea; art; symbol; image; Мyth